2005
DOI: 10.1097/01.ccx.0000155354.78617.91
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influences on outcome following acute neurological insults

Abstract: There is evidence demonstrating the epsilon4 allele of APOE predisposes to poor outcome after TBI, hemorrhagic stroke and SAH, but not ischemic stroke. The reason for this difference is unclear but it suggests there may be differences in the key mechanisms underlying the response to different types of insult. The role of other gene polymorphisms is being increasingly explored but there is still a need for larger prospective studies looking at larger panels of gene polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…The potential role of ApoE in the repair and regeneration of neurons and survival after brain injury was found in rodent models of head injury and ischaemic stroke (Graham et al 1999;Horsburgh et al 2000). Clinical studies have shown that genotypes with the e 4 allele are associated with poor outcome after head injury (Waters and Nicoll 2005). According to these observations, it can be suggested that ApoE might influence outcome after acute stroke in humans (Waters and Nicoll 2005).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The potential role of ApoE in the repair and regeneration of neurons and survival after brain injury was found in rodent models of head injury and ischaemic stroke (Graham et al 1999;Horsburgh et al 2000). Clinical studies have shown that genotypes with the e 4 allele are associated with poor outcome after head injury (Waters and Nicoll 2005). According to these observations, it can be suggested that ApoE might influence outcome after acute stroke in humans (Waters and Nicoll 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Clinical studies have shown that genotypes with the e 4 allele are associated with poor outcome after head injury (Waters and Nicoll 2005). According to these observations, it can be suggested that ApoE might influence outcome after acute stroke in humans (Waters and Nicoll 2005). Since different studies have produced conflicting results, there was the necessity of the conducting of a comprehensive meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…32,87 Further, variability in the trajectories of the diffusion measures might be affected by differences in number of previous concussions, 68 timing of each athlete's return to play (see Table 1), and individual genetic predisposition. 88,89 Experimental designs of future studies should include the assessment of subconcussive hits, extending at least to the end of season.…”
Section: Longitudinal Dti Study Of Wm Tracts After Srcmentioning
confidence: 99%
“…68,69 Apolipoprotein E is a key protein that plays an essential role in the repair of cell membrane and spread of neuritis following injury. 9,34,49 This protein is controlled by a gene with 3 primary alleles (e2, e3, and e4).…”
Section: Involvement Of Genetic Polymorphismsmentioning
confidence: 99%